The effects of PM2.5 on asthmatic and allergic diseases or symptoms in preschool children of six Chinese cities, based on China, Children, Homes and Health (CCHH) project. (January 2018) - Chen, Fei'er; Lin, Zhijing; Chen, Renjie; Norback, Dan; Liu, Cong; Kan, Haidong; Deng, Qihong; Huang, Chen; Hu, Yu; Zou, Zhijun; Liu, Wei; Wang, Juan; et al.
Abstract: The urbanization and industrialization in China is accompanied by bad air quality, and the prevalence of asthma in Chinese children has been increasing in recent years. To investigate the associations between ambient PM2.5 levels and asthmatic and allergic diseases or symptoms in preschool children in China, we assigned PM2.5 exposure data from the Global Burden of Disease (GBD) project to 205 kindergartens at a spatial resolution of 0.1° × 0.1° in six cities in China (Shanghai, Nanjing, Chongqing, Changsha, Urumqi, and Taiyuan). A hierarchical multiple logistical regression model was applied to analyze the associations between kindergarten-level PM2.5 exposure and individual-level outcomes of asthmatic and allergic symptoms. The individual-level variables, including gender, age, family history of asthma and allergic diseases, breastfeeding, parental smoking, indoor dampness, interior decoration pollution, household annual income, and city-level variable-annual temperature were adjusted. A total of 30, 759 children (average age 4.6 years, 51.7% boys) were enrolled in this study. Apart from family history, indoor dampness, and decoration as predominant risk factors, we found that an increase of 10 μg/m 3 of the annual PM2.5 was positively associated with the prevalence of allergic rhinitis by an odds ratio (OR) of 1.20 (95% confidence interval [CI] 1.11, 1.29) and diagnosed asthma by OR of 1.10 (95% CI 1.03, 1.18). Those who lived in non-urban (vs. urban) areas were exposed to more severe indoor air pollution arising from biomass combustion and had significantly higher ORs between PM2.5 and allergic rhinitis and current rhinitis. Our study suggested that long-term exposure to PM2.5 might increase the risks of asthmatic and allergic diseases or symptoms in preschool children in China. Compared to those living in urban areas, children living in suburban or rural areas had a higher risk of PM2.5 exposure. Graphical abstract: Highlights: Long-term ambient PM2.5 can be risky for childhood asthmatic and allergic disorders. Children in suburban/rural areas might be at higher risks to PM2.5 than urban children. Children with less breastfeeding were more susceptible to PM2.5 on diagnosed asthma. Children with indoor dampness were more susceptible to PM2.5 on diagnosed asthma. Abstract : Ambient PM2.5 is associated with asthma and allergic diseases and symptoms in Chinese preschool children.